English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-06-25 00:57:48 · 9 answers · asked by 23344 2 in Science & Mathematics Mathematics

Elimination method:
3x-5y=-2
5y-3x=7

2007-06-25 01:40:25 · update #1

9 answers

Rearrange the second equation to line up the variables:

2x - 5y = -2
-3x +5y = 7

The y-variable cancels without having to do anything extra, so:

-x = 5

or

x = -5

Plugging this back into one of the original equations:

-3(-5) + 5y = 7

15 + 5y = 7

5y = -8

y = -8/5

So the answer is x = -5 and y = -8/5

2007-06-25 01:04:10 · answer #1 · answered by mattside_bic 2 · 0 0

I did the maths, too and my result was x=-5, y=-8/5.

Here is a very detailed script of how I did it.

2x-5y=-2
5y-3x=7

2x-5y=-2
-3x+5y=7

-5y=-2-2x
5y=2+2x
y=(2+2x)/5

-3x=(2+2x)=7
2+2x=7+3x
2x=5+3x
-x=5
x=-5

-3x+5y=7
15+5y=7
5y=-8
y=-8/5

I hope it helps you understand the whole thing!

2007-06-25 01:12:17 · answer #2 · answered by Anonymous · 0 0

2x -5y = -2 Rearrange 2nd equation:
-3x + 5y= 7 add:
----------------
-x = 5 divide thru by -1:
x = -5
Substitute into 1st equation:
2(-5) - 5y = -2
-10 -5y = -2
-5y = 8
y = -8/5
(-5,-8/5)

2007-06-25 01:11:33 · answer #3 · answered by gm 2 · 0 0

2x-5y=-2
5y-3x=7

change 2x-5y=-2 to 5y-2x=2
cancel out 5y
-2x = 2
-3x = 7
-5x = 9
x = -5/9

2007-06-25 01:02:10 · answer #4 · answered by Mike 4 · 0 1

2x - 5y = -2
+
-3x +5y = 7
___________
-x = 5 => x= - 5

plug in and you get y = -8/5

2007-06-25 01:01:44 · answer #5 · answered by S 2 · 0 0

2x-5y=-2.......(1)
-3x+5y=7.....(2)(all terms on same place)
so (y) gets canceled and...
-x=5
x=-5
substitute x=-5 in (1)
2(-5)-5y=-2
-10-5y=-2
-5y=-2+10
-5y=8
-y=8/5
y=-8/5
y=-1.6
hope tis is nt for ur maths home work.... heeeee......!

2007-06-25 01:42:17 · answer #6 · answered by Aravinthan J 2 · 0 0

2x-5y=-2---let it be equation 1.
-3x+5y=7---let it be equation 2.
multiply equation 1. by -3 & equation 2.by 2
Therefore it becomes
-6x+15y=6
-6x+10y=14

substract both(NOTE:sign will change due 2 substraction)

Solving both u get
5y=-8
Therefore y=-8/5

putting value of y in equation 1.,,we get
2x-5*-8/5
solving this, we get
2x=-10
there fore x=-5

So ,ur answers r
x=-5
y=-8/5

Take care
bye

2007-06-25 01:18:56 · answer #7 · answered by Anonymous · 0 0

2x - 5y = - 2
-3x + 5y = 7-----ADD
- x = 5
x = - 5
5y + 15 = 7
5y = - 8
y = - 8/5
SOLUTION
x = - 5 , y = - 8/5

2007-06-27 22:00:01 · answer #8 · answered by Como 7 · 0 0

2x-5y=-2 +
5y-3x=7
__________
2x-3x=5
=>x=-5

2007-06-25 01:02:26 · answer #9 · answered by Anonymous · 0 0

fedest.com, questions and answers